2009
DOI: 10.1016/j.disc.2008.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Optimal gathering protocols on paths under interference constraints

Abstract: We study the problem of gathering information from the nodes of a multi-hop radio network into a predefined destination node under reachability and interference constraints. In such a network, a node is able to send messages to other nodes within reception distance, but doing so it might create interference with other communications. Thus, a message can only be properly received if the receiver is reachable from the sender and there is no interference from another message being simultaneously transmitted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Other related results can be found in [1,2,6,7,10] (see [9] for a survey). In these articles data buffering is allowed at intermediate nodes, achieving a smaller makespan.…”
Section: Related Workmentioning
confidence: 78%
See 1 more Smart Citation
“…Other related results can be found in [1,2,6,7,10] (see [9] for a survey). In these articles data buffering is allowed at intermediate nodes, achieving a smaller makespan.…”
Section: Related Workmentioning
confidence: 78%
“…For simplicity we suppose that the grid is infinite; however it suffices to consider a grid slightly greater than the one containing all the destinations of messages. Note that our work does not include the case of the paths, already considered in [1,11,15].…”
Section: Notations and Lower Boundmentioning
confidence: 99%
“…A heuristic on-line algorithm is proposed and the simulations show the good performances of the algorithm. In [6,8,7], the quantity that is optimized is the data latency. The authors compute tight bounds of the minimal number of rounds that are required for solving the problem.…”
Section: Introduction Our Contribution and Related Workmentioning
confidence: 99%
“…An appropriate scheduling of the transmissions avoids collision. In [35,6,8,7], the authors discuss the problem of determining the optimal scheduling. In [35], the quantity that is optimized is the energy consumption.…”
Section: Introduction Our Contribution and Related Workmentioning
confidence: 99%
“…The wireless gathering problem in a centralized setting was studied by Bermond et al [4][5][6] and Bonifaci et al [7,8]. Bermond et al [5] showed that the problem of minimizing maximum completion time is NP-hard, even when all release times are zero.…”
Section: Introductionmentioning
confidence: 99%